Microstructure, Mechanical Properties, Degradation Behavior, and Implant Testing of Hot-Rolled Biodegradable ZKX500 Magnesium Alloy - Ying-Ting Huang (MDPI AG, 2021)
Currently, orthopedic metallic implants are mostly made of stainless steel and titanium alloys. After healing, patients are usually required to undergo a secondary surgery for implant removal, which not only poses a medical risk but also costs medical resources. Magnesium-based biodegradable implants that can be absorbed by humans promote osteoblastic activity during the degradation and inhibit the formation of osteoclasts. Moreover, magnesium can be detected by X-ray, and this can help doctors to perform postoperative diagnosis and treatment, which is beneficial for patients. In this study, a ZKX500 Mg alloy bone plate was prepared through rolling. In addition to the microstructure and the mechanical properties of the hot-rolled ZKX500 Mg alloy, its in vitro corrosion behavior under different heat treatment conditions is discussed. A 6-month mini-pig implantation test was conducted using the fabricated ZKX500 Mg alloy bone plate and bone screws. The in vivo degradation mechanism and new bone formation were observed using computed tomography images. The pig recovered well, and the results can serve as an important reference for clinical applications. In addition, another important contribution of this study is that it can help the field of orthopedics to better understand the biodegradable magnesium alloy.